Emerging trends of public administration in post NPM ERA: Strategies and prospects - Nayak, Bibhuti Bhusan and Mahapatra, Padmalaya (South Asian Journal of Socio-Political Studies)
As an academic discipline, Public Administration is growing and developing gradually. Always it has tried to respond to the constantly emerging social needs. Some of the significant contemporary development in this discipline is the New Public Administration, New Public Management and theory and practice of public policy. Public Administration as a field of inquiry is comparatively of recent origin. Since inception, it has passed through various stages of evolution to reach in its present form. Broadly, five stages viz. the Politics/Administration Dichotomy, the Principles of Administration, Criticisms and Challenges, Crisis of Identity and Public Administration as an Independent discipline have been identified. An attempt has been made to understand the present status of discipline. The Emerging trends of Public Administration in post NPM Era: Current Strategies and Future Prospects represent a critical evaluation of the nature and impact of new public management, reflecting the latest thinking in the field. The article offers a comprehensive analysis of the emerging trends of public administration in post NPM era from both theoretical and practical view points.- Reproduced
Keywords: New public administration, New public management, Strategies, Prospects and dichotomy